Consumer involvement with corporate reputation - Anlaş, Selcen. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
This thesis aimed to comprehend the underlying motivations of the consumers that make them get involved with the corporate reputation (CR) of companies across purchase decision contexts. It presented a model of consumer involvement (CI) with CR and scrutinized its underlying motivational states and its impact on the word of mouth (WOM) behavior of consumers. We introduced a new construct and, accordingly, a new scale to the literature: Corporate Reputation Involvement (CRI). The theoretical model and all hypothesized interactions between the model's constructs were developed based on the theoretical tenets of Regulatory Focus Theory (RFT) and CI. We empirically tested the proposed model with data from 420 consumers in Turkey. The collected data was analyzed using the Partial Least Square Structural Equation Modeling to assess the measurement and structural models. The different impacts of different regulatory focuses on the CRI confirmed that RFT effectively explains the individual differences regarding CRI. It was found that the pivotal role of CR in consumers' purchase decision making is beyond its mostly referred role in mitigating perceived risk and uncertainty related to the decision. The findings highlight that consumers get involved with CR to attain positive outcomes related to their goals, such as perceived benefits, positive emotions, and self-needs. The different impacts of CRI on WOM were concluded. The findings will help marketing scholars better understand whether and why (the underlying motivations) consumers get involved with the CR of companies. It will also help marketing professionals guide their companies in designing and executing appropriate marketing strategies and programs.
Keywords: Consumer behavior.; Regulators (Mathematics)